Perlindungan Hukum bagi Pekerja Dengan Perjanjian Kerja Tidak Tertulis pada Perusahaan Pemberi Kerja - Robertus Berli Puryanto; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2021)
Labor is something that is needed by an employing company in carrying out its economic activities. This can be seen in the constitutional arrangements of the Republic of Indonesia in Article 27 paragraph (2) of the 1945 Constitution of the Republic of Indonesia. In the implementation of the working relationship between workers and the employing company, there are several rights and obligations that must be fulfilled between the two parties. Because there are provisions regarding work agreements that are differentiated based on the form of the agreement, each worker has different rights where these rights must be guaranteed by the company based on law. From this, the problems that will be examined are legal protection for workers with an unwritten work agreement at the employing company, as well as legal remedies that can be taken by workers with an unwritten agreement in the event of a violation of rights by the company. The research method used is normative legal research, namely legal research conducted by examining existing library materials. By examining problems by looking at existing regulations, and describing problems that occur in practice or in everyday life in society. From the research conducted, it was found that legal protection for workers with an unwritten work agreement at the employing company is regulated based on Law Number 13 of 2003 concerning Manpower where the basis is that the applicable work agreement is an indefinite work agreement so that the rights obtained under the provisions of the law. Then efforts that can be made if there is a violation of the law in work relations is based on Law Number 20 of 2004 concerning Industrial Relations Dispute Settlement, namely in the form of Bipartite, Tripartite (Mediation, Consoliation and Arbitration) negotiations, as well as through Trials at the Industrial Relations Court.